EFEKTIVITAS MANAJEMEN JALAN NAPAS TERHADAP PENURUNAN DISPNEA PADA PASIEN CONGESTIVE HEART FAILURE DI RUANG IGD RSUD LABUANG BAJI - Muh. Faidil; Tutik Agustini; Suci Hardiyanti Suharto Putri; Sudarman (CV. Adiba Aisha Amira, 2025)
Congestive Heart Failure (CHF) is a progressive clinical syndrome characterized by the inability of the heart to pump blood adequately, causing a decrease in tissue perfusion and symptoms such as dyspnea, orthopnea, and fatigue. Dyspnea is one of the main complaints of CHF patients. This case study aims to determine the effectiveness of airway management, especially through semi-fowler position adjustment, in reducing the level of dyspnea in patients with Congestive Heart Failure in the emergency room of Labuang Baji Hospital Makassar. This study uses a case study design with a nursing process approach that includes assessment, diagnosis, intervention, implementation, and evaluation. The subject was a 54-year-old male patient with a medical diagnosis of CHF, the main complaint of shortness of breath. After 8 hours of nursing intervention, patients showed a decrease in the level of shortness of breath, improvement in breathing patterns, increased oxygen saturation up to 98–99%, and stabilization of vital signs. Patients also report improved comfort and better sleep quality. The conclusion of the study is that airway management through the application of the semi-fowler position has been shown to be effective in reducing dyspnea in patients with congestive heart failure. This intervention can be recommended as one of the simple, effective, and easily applied non-pharmacological measures in the emergency department and treatment room.